2010
DOI: 10.1094/phyto-100-9-0922
|View full text |Cite
|
Sign up to set email alerts
|

Extending the Fungal Host Range of a Partitivirus and a Mycoreovirus from Rosellinia necatrix by Inoculation of Protoplasts with Virus Particles

Abstract: The potential host range of mycoviruses is poorly understood because of the lack of suitable inoculation methods. Recently, successful transfection has been reported for somatically incompatible fungal isolates with purified virus particles of two mycoviruses, the partitivirus RnPV1-W8 (RnPV1) and the mycoreovirus RnMyRV3/W370 (MyRV3), from the white root rot fungus Rosellinia necatrix (class Sordariomycetes, subclass Xylariomycetidae). These studies examined and revealed the effect of the mycoviruses on growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
59
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 42 publications
2
59
0
Order By: Relevance
“…However, its artificial introduction into C. parasitica may perturb such a relationship and induce symptoms. A similar phenomenon was previously observed for another partitivirus from R. necatrix (RnPV1), which enhanced pigmentation in C. parasitica but showed asymptomatic infection in the natural host, R. necatrix (56). The presence of DI-dsRNA1 is associated with reduced symptom severity in either C. parasitica strain (Fig.…”
Section: Discussionsupporting
confidence: 84%
“…However, its artificial introduction into C. parasitica may perturb such a relationship and induce symptoms. A similar phenomenon was previously observed for another partitivirus from R. necatrix (RnPV1), which enhanced pigmentation in C. parasitica but showed asymptomatic infection in the natural host, R. necatrix (56). The presence of DI-dsRNA1 is associated with reduced symptom severity in either C. parasitica strain (Fig.…”
Section: Discussionsupporting
confidence: 84%
“…In the present study, the protocol has been applied to RnVV1, the first victorivirus whose host range has been expanded experimentally. As in the case for the partitiviruses (RnPV1 and RnPV2) from R. necatrix (17,65), C. parasitica, belonging to an order Diaporthales different from the Xylariales accommodating R. necatrix, was shown by transfection assay to support the replication of RnVV1. We are now attempting to determine whether RnVV1 can infect organisms differing at taxon levels higher than class.…”
Section: Discussionmentioning
confidence: 73%
“…However, experiments using infectious cDNA clones or synthetic transcripts have shown that the prototype hypovirus replicates in fungal species of the same family (63) or a different one within the same order as that of its natural host, the chestnut blight fungus C. parasitica (64). The virion transfection protocol has also provided chance to expand the host range of mycoviruses, such as RnPV1 and MyRV3 (65). In the present study, the protocol has been applied to RnVV1, the first victorivirus whose host range has been expanded experimentally.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, phylogenetic analysis of the coat protein sequences of some partitiviruses revealed that incidences of horizontal gene transfer had occurred between viruses and eukaryotic organisms (18,19). A system in which partitivirus particles (i.e., Rosellinia necatrix partitivirus 1-W8 [RnPV1-W8]) can be transfected into fungal protoplasts has been successfully established and was utilized to confirm that RnPV1-W8 has a broad host range in Sordariomycetes (23,24). Particle structures determined by cryo-electron microscopy (cryo-EM) and three-dimensional (3D) image reconstruction, as well as one determined by X-ray crystallography, have shown three different partitivirus capsids to have a so-called "Tϭ2" organization comprising 60 capsid protein (CP) dimers arranged on a Tϭ1 icosahedral lattice (25)(26)(27).…”
mentioning
confidence: 99%